Obravnava prestopov nogometnih igralcev v okvirih notranjega trga - Škalič Müller, Valentina (Podjetje in delo, 2024)
The article addresses the complex issue of transfers of professional football players. The first part presents the influence of the European Union on the sports sector and describes how the European Union has intervened in the field of football. The second part of the contribution focuses on a detailed examination of the procedures for the transfers of football players, with an emphasis on the operations of the FIFA sports organisation. The European Union is one of the stakeholders increasingly involved in the sports sector. Through the case law of the Court of Justice of the European Union, the role of sports in the legal system of the European Union is strengthened. Sports are primarily affected by the rules of the internal market of the European Union, especially concerning the issue of the transfer of athletes. As workers, professional athletes have the freedom to choose which employers they will enter into an employment contract with - in this case, the employers are sports clubs. However, despite this freedom, they often encounter obstacles and limitations that prevent or hinder their free movement between clubs. This poses challenges to the realisation of the free movement of workers in the light of European Union law. The most attention in athlete transfers is given to the football industry, as football, as a modern branch of the economy, represents top-level professional sports. Indeed, transfers of football players are complex processes involving various stakeholders and often pose problems within the European Union due to potential violations of EU internal law.
Keywords: Bosman; Bosman ruling; FIFA; football player transfers; free movement of workers; internal market; notranji trg; prestop nogometnih igralcev; prosti pretok delavcev; sports law; športno pravo; transferji; transfers